KINERJA KEUANGAN, UKURAN PERUSAHAAN, GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Tasum Tasum (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study was conducted with the main objective of providing empirical evidence on the influence of several factors on sustainability report disclosure. The type of research conducted in this study was quantitative with a descriptive approach. This study discusses the relationship between good corporate governance, financial performance, and company size on the quality of disclosure in sustainability reports (a case study of banking sector companies listed on the Indonesia Stock Exchange for the period 2020-2022). The population in this study consisted of 44 companies. The sample data used in this study consisted of 23 banking companies that published sustainability reports during the three-year period from 2020 to 2022. The sampling technique used was purposive sampling using SPSS version 29 software. The conclusion obtained is that profitability, the board of directors, and the board of commissioners do not have a significant effect on sustainability reports. Meanwhile, leverage, firm size, and the audit committee have a significant effect on sustainability reports.